1996
DOI: 10.1103/physrevlett.77.2069
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Excitations of the Doped-Hole State in DiamagneticLa2Cu0.5Li0.5<

Abstract: Substitution of Li for Cu in La 2 Cu 12x Li x O 4 donates holes; at x 0.5 the Li ions form an ordered superlattice which isolates individual CuO 4 plaquettes from one another, and the number of doped holes is sufficient that each plaquette is occupied. Above 170 K, an activated temperature dependence of the Cu nuclear spin relaxation rate reveals a magnetic excitation of the doped-hole state with an energy of ϳ130 meV. Below 170 K relaxation is primarily due to fluctuations of the electric field gradient; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In the cuprates the doped holes are believed to occupy oxygen 2p orbitals which hybridize with the Cu 3d x 2 Ϫy 2 orbital to form a d 9 L (L ligand hole͒ configuration. 4,5 It is possible to vary the electron density in the square lattice by doping such a compound to La 2Ϫx Sr x CuO 4 , and then x measures the density of holes relative to the insulating state with one electron per site. 6,7 Compared with the substitution of La 3ϩ by the 2ϩ ions, the substitution by monovalent ions, such as H ϩ , Li ϩ , Na ϩ , K ϩ , or Rb ϩ , should be more effective to provide holes which are crucial to the superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the cuprates the doped holes are believed to occupy oxygen 2p orbitals which hybridize with the Cu 3d x 2 Ϫy 2 orbital to form a d 9 L (L ligand hole͒ configuration. 4,5 It is possible to vary the electron density in the square lattice by doping such a compound to La 2Ϫx Sr x CuO 4 , and then x measures the density of holes relative to the insulating state with one electron per site. 6,7 Compared with the substitution of La 3ϩ by the 2ϩ ions, the substitution by monovalent ions, such as H ϩ , Li ϩ , Na ϩ , K ϩ , or Rb ϩ , should be more effective to provide holes which are crucial to the superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…A most direct and convincing observation of the hole singlet-triplet PJT centers is made recently [5] by the NQR method in La 2 Cu 0.5 Li 0.5 O 4 . The authors revealed the spin singlet ground state (S = 0) and the low lying spin triplet state (S = 1) with the singlet-triplet separation ∆ ST = 0.13eV comparable with the well known estimates for the nearest neighbours exchange interactions for the parent cuprates.…”
mentioning
confidence: 97%
“…In this connection note the paper [20] whose authors undertook an NQR study of the isolated hole centers in La 2 Cu 0X5 Li 0X5 O 4 . They have revealed the spin singlet ground state (S 0) and the low lying spin triplet state (S 1) with the singlet-triplet separation D ST 0X13 eV.…”
Section: The Pjt Centers In Magnetic Resonancementioning
confidence: 98%